Civil war in ancient Greece and Rome: contexts of disintegration and reintegration - Börm, Henning; Mattheis, Marco; Wienand, Johannes (Heidelberger althistorische Beiträge und epigraphische Studien, 2016)
"[...]the Collaborative Research Center The Dynamics of Ritual at the University of Heidelberg and the Center of Excellence Cultural Foundations of Integration at the University of Konstanz jointly organized an international conference in 2011 at Schloss Reisenburg near Günzburg in Southern Germany." (Preface)
Literaturangaben
Keywords: Konferenzschrift -- 2011 -- Günzburg-Reisensburg; Aufsatzsammlung; Bürgerkrieg; Römisches Reich; Griechenland